Konstruksi Makna Larangan Wisata Pantai Selatan Bagi Santri PPRU 1 (Analisis Etnografi) - Abid Masluhir Rifqi; Kholik Kholik (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study analyzes the impact of the ban on visiting the south coast on students of Raudlatul Ulum 1 Islamic Boarding School (PPRU 1) through a qualitative method with an ethnographic approach. This study investigates the cultural, religious, and social reasons that underlie the ban through active participant observation and interviews. The results of the study indicate that the ban for PPRU 1 students to instill obedience to existing rules and the beauty of the South Coast has more than one meaning and is a multifaceted phenomenon. The ban is not only influenced by mystical beliefs about supernatural powers that exist on the South Coast, but is also deeply internalized with religious values, discipline, and the identity of the students. This ban ensures action as a mechanism of social control of the order and sanctity of the pesantren environment. In addition, this ban creates social boundaries between students and members of society and increases social cohesion among students. The study also reveals that this ban is not a rigid and absolute rule. There are gray nuances in its application, depending on the status of a person's santri and the purpose of the visit to the South Coast. This study contributes by showing the complexity of cultural phenomena in the pesantren environment. The research findings can be included as considerations in the planning and implementation of educational programs in Islamic boarding schools, as well as in efforts to maintain cultural and religious values ​​behind the ban.